World Federation of Interventional and Therapeutic Neuroradiology (WFITN) Federation Assembly neurointerventional surgery safety checklist - Chen, Michael; Fargen, Kyle M; Mocco, J.; Siddiqui, Adnan H.; Miyachi, Shigeru; Mahadevan, Jeyaledchumy; Na Ayudya, Sirintara Singhara; Churojana, Anchalee; Chryssidis, Steve; De Villiers, Laetitia; Rahman, Mohibur; Dey, Subash Kanti; et al. (BMJ, 2023)
Over the last 10 years, there has been a rise in neurointerventional case complexity, device variety and physician distractions. Even among experienced hysicians, this trend challenges our memory and concentration, making it more difficult to remember safety principles and their implications. Checklists are regarded by some as a redundant exercise that wastes time, or as an attack on physician autonomy. However, given the increasing case and disease complexity along with the number of distractions, it is even more important now to have a compelling reminder of safety principles that preserve habits that are susceptible to being overlooked because they seem mundane. Most hospitals have mandated a pre-procedure neurointerventional time-out checklist, but often it ends up being done in a cursory fashion for the primary purpose of ‘checking off boxes’. There may be value in iterating the checklist to further emphasize safety and communication. The Federation Assembly of the World Federation of Interventional and Therapeutic Neuroradiology (WFITN) decided to construct a checklist for neurointerventional cases based on a review of the literature and insights from an expert panel.
Keywords: Angiography; Intervention; Standards; Technique